Urban waterfront regeneration as a response to promote tourism and encourage socio activities at Victoria City, Wilayah Persekutuan Labuan - Alias, Mohd Hazwan (2018)
Victoria is not yet being discovered as a potential area for tourist but Labuan town has its own attraction and uniqueness, characterized by long stretch seaside area. Labuan is in a merge of development to promoting Labuan as one of a tourist destination and to be known by outsiders. In January 2018, the media’s get attention towards the development of the Labuan-Menumbok bridge that will link Labuan and Sabah to developed a successful polycentric centre development created to increase connectivity to the influential region. The implication of a new bridge development making the port area at Labuan become a waterfront area according to Labuan Blueprint 2030. Therefore, this project is to find a solution on how the implementation of a Landscape design helps to attract the local surrounding and visitor from the inner city through the waterfront. Furthermore, to proposed an urban activity that will set as a major destination for the people so that it will become a successful Waterfront area at Labuan City. The design implementation is using the integrative theory of urban design approach to strengthen the sense of place in the urban area that allows for contextual integration to take place by using a specific design principle that consist of good form, vitality, legibility, meaning and comfort. Using the image of the city as a design approach also help to hinder the navigation of people at the urban area. The primary purposes of the solution are to improve the city connectivity throughout the waterfront that will improve Labuan city urban environment. Last but not Least, the new development of Labuan Waterfront will create one of the spot tourisms at Labuan in creating Labuan knowable throughout the regional level.